(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Alcohol’s role in men’s violence against women is a controversial issue. Many articles have been written that we read in the newspapers that teens are being held for consuming drugs & alcohol and most of them are usually aged between 17-20. But the main question arises that why the Indian society is experiencing such a dilemma where more of the teenagers and youths are involved in unethical, non-societal and unproductive activities like substance or drug abuse. This research paper studies about domestic violence, drug / alcohol abuse and types of anger in Indian culture in India and abroad.